Enhancing Public Service Effectiveness through Work Discipline and Information Technology Utilization in Archipelagic Local Government Contexts - Andini Aulia; Edi Jusriadi; Sri Andayaningsih (www.amertainstitute.com, 2026)
This study examines the influence of work discipline and the utilization of information technology on the effectiveness of public services at the East Pasimasunggu Subdistrict Office, Selayar Islands Regency. Public service delivery in archipelagic regions faces structural challenges, including geographical dispersion, limited infrastructure, and uneven human resource capacity. A quantitative approach was employed using census sampling, involving all 38 administrative staff as respondents. Data were collected through structured questionnaires, observation, and documentation, and analyzed using multiple linear regression. The results indicate that both work discipline and information technology utilization have a positive and significant effect on public service effectiveness, both partially and simultaneously. Work discipline emerges as the dominant factor, reflecting the importance of punctuality, rule compliance, and responsibility in ensuring consistent service delivery. Meanwhile, the utilization of information technology contributes to improved efficiency, accuracy, and service speed, although its implementation remains constrained by technical and competency limitations. The coefficient of determination (R²) of 0.713 suggests that 71.3% of the variation in public service effectiveness is explained by the two independent variables, while the remaining 28.7% is influenced by other factors. These findings highlight the need for strengthening employee discipline and enhancing digital capabilities to optimize public service performance, particularly in geographically challenging regions.